2020
DOI: 10.1108/ribs-03-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Strategic change: the impact of senior foreign managers, firm size and uncertainty avoidance

Abstract: Purpose This study aims to examine how senior foreign executives in a top management team catalyse strategic change in firms that originated from emerging markets (EMs). It further examines the moderating effects of organisational size and uncertainty avoidance (UA) on the positive relationship between senior foreign manager and strategic change in an organisation. Design/methodology/approach The panel data econometrics and multilevel analyses were adopted to run the model. The author tests hypotheses on 263… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 99 publications
(182 reference statements)
0
16
0
Order By: Relevance
“…Indonesia was the research context, Indonesia was the research context, a country with a high-power distance culture and higher uncertainty avoidance. The degree of uncertainty avoidance influences employee empowerment (Randolph and Sashkin, 2002) and strategic change (Kalasin, 2020). Therefore, it is important to replicate this investigation in different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia was the research context, Indonesia was the research context, a country with a high-power distance culture and higher uncertainty avoidance. The degree of uncertainty avoidance influences employee empowerment (Randolph and Sashkin, 2002) and strategic change (Kalasin, 2020). Therefore, it is important to replicate this investigation in different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Firms deal with significant uncertainty in the years surrounding IPO. IPO firms may face challenges in cultures avoidant of uncertainty because such cultures tend to resist new approaches and are likely to conform to existing norms (Kalasin, 2020). For instance, Thai culture is more avoidant of uncertainty than Vietnamese culture; therefore, entrepreneurial actions such as risk-taking are more valued in Vietnamese firms (Swierczek and Ha, 2003).…”
Section: Uncertainty Avoidancementioning
confidence: 99%
“…For instance, Thai culture is more avoidant of uncertainty than Vietnamese culture; therefore, entrepreneurial actions such as risk-taking are more valued in Vietnamese firms (Swierczek and Ha, 2003). Given hesitancy toward new approaches, uncertainty-avoidant cultures weaken the ability of managers to enact change (Kalasin, 2020). Key benefits of a founder's human capital are the ability to be transformative (Ling et al, 2008), make strategic decisions swiftly (Souder et al, 2012) and tolerate uncertainty and unanticipated changes (de Luque and Javidan, 2004).…”
Section: Uncertainty Avoidancementioning
confidence: 99%
“…Popov et al (2019) found that we must consider cultural disparities to promote inter-firm cooperation at international companies. According to Kalasin (2021), senior foreign managers are active agents who can promote and implement essential changes because they possess different value sets, knowledge and experience. In effect, cultural differences among senior managers benefit organizations.…”
Section: Ribs 324mentioning
confidence: 99%